125k views
21 votes
What is the equation 8x-3y=6-4x in Stanford form?

User Richa Garg
by
4.8k points

1 Answer

4 votes

Answer:


12x - 3y = 6

Explanation:

Standard form is written this way:
Ax+By=C

However, in this case, we just have to simplify 8x-3y=6-4x, as it is already mostly in standard form.

So, to do this, we have to combine like terms.

The only like terms that can be combined are -4x and 8x.

So, we add 4x to both sides, and we get:
12x - 3y = 6.

User Ojdo
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.